Forward Guidance without Common Knowledge - Angeletos, George-Marios; Lian, Chen (American Economic Review, 2018)
How does the economy respond to news about future policies or future fundamentals? Standard practice assumes that agents have common knowledge of such news and face no uncertainty about how others will respond. Relaxing this assumption attenuates the general equilibrium effects of news and rationalizes a form of myopia at the aggregate level. We establish these insights within a class of games which nests, but is not limited to, the New Keynesian model. Our results help resolve the forward-guidance puzzle, offer a rationale for the front-loading of fiscal stimuli, and illustrate more broadly the fragility of predictions that rest on long series of forward-looking feedback loops. (JEL D82, D83, D84, E12, E23, E52, E62)